2021
DOI: 10.2147/jir.s340745
|View full text |Cite
|
Sign up to set email alerts
|

Composite Inflammatory Indicators as Early Predictor of Intra-abdominal Infections after General Surgery

Abstract: Objective To identify rapid and accurate early diagnostic indicators for intra-abdominal infection (IAI) after general surgery. Methods We conducted a retrospective analysis of 3,810 general surgical patients in our hospital from August 2017 to July 2018. The predictive value of PCT, CRP, TNFα, and IL6 on postoperative days (PODs) 1 and 3 and composite indicators for complicated IAIs among surgical patients was clarified. Results There were 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Since it increases in correlation with the severity and duration of the infection, this marker is a valuable marker for predicting the prognosis and outcome of patients with sepsis. 38 In a recent study, Song et al 38 found that serum expression of TNF-α and IL-6 were associated with IAIs in patients after surgery. A composite of IL-6, PCT, and TNF-α can also increase the reliability of the prediction of postoperative infections.…”
Section: Interleukin-6mentioning
confidence: 99%
“…Since it increases in correlation with the severity and duration of the infection, this marker is a valuable marker for predicting the prognosis and outcome of patients with sepsis. 38 In a recent study, Song et al 38 found that serum expression of TNF-α and IL-6 were associated with IAIs in patients after surgery. A composite of IL-6, PCT, and TNF-α can also increase the reliability of the prediction of postoperative infections.…”
Section: Interleukin-6mentioning
confidence: 99%